Kuala Selangor perceived attractiveness as a domestic tourism destination / Hasan Mohamed Zakaria and Azlizam Aziz - Mohamed Zakaria, Hasan; Aziz, Azlizam (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2018)
This study aims to provide a more in-depth knowledge of visitors' perceived attractiveness of a destination. The role of the perceived importance of an attractiveness attribute and the ability of the destination to fulfill visitors' need was assessed using the Multi Attribute Model. Survey was conducted at multiple attraction sites in Kuala Selangor. A total of 390 responses were analyzed using SPSS 23 software program. The result found that heritage, history, and cultural attraction attractiveness attribute was perceived as the most important factor and having the highest ability to satisfy the needs of the visitors. This result provides information on how domestic visitors perceive the attractions in Kuala Selangor and on which attribute to be focused by destination marketers for future marketing strategy.